1972
DOI: 10.1144/sjg08030179
|View full text |Cite
|
Sign up to set email alerts
|

Dating events in the Metamorphic Caledonides: impressions of the symposium held in Edinburgh, September 1971

Abstract: SYNOPSISThe symposium comprised seventeen contributions on the following subjects: palaeontological evidence for the age of the Dalradian, the Ordovician of western Ireland and other formations relevant to the dating of events (2 papers); the sequence of tectonothermal events in parts of the Moine Thrust Belt and the Moine Nappe (4 papers); deformation rates (1 paper); isotope ages and their relation to events in the Moinian and Dalradian areas (4 papers); early events in the Scandinavian Caledonides and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Thus, Flinn & Pringle (1976) regard an Rb-Sr whole-rock isochron age of 530-25 Ma for the Colla Firth migmatite of Shetland as in complete agreement with ages of migmatisation from Connemara (520+--30 Ma, Dunning 1972), Norway (530-+35 Ma, Pringle & Sturt 1969) and consistent with that for the Duchray Hill migmatite reported here.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, Flinn & Pringle (1976) regard an Rb-Sr whole-rock isochron age of 530-25 Ma for the Colla Firth migmatite of Shetland as in complete agreement with ages of migmatisation from Connemara (520+--30 Ma, Dunning 1972), Norway (530-+35 Ma, Pringle & Sturt 1969) and consistent with that for the Duchray Hill migmatite reported here.…”
Section: Discussionsupporting
confidence: 83%
“…5 ) it is clear that pre-Permian palaeomagnetic pole positions do not all fall on a single common polar path. On the contrary, Briden (1971) (also quoted by Dunning (1972) and illustrated in Smith et al (1973)) first showed that three distinct regions with distinct polar paths are evident, namely Gondwanaland, Siberia and Euramerica (all of Europe and North America north of the Hercynian-Alleghenian orogenic belt). Each of these regions may be regarded to a first approximation as a Palaeozoic crustal plate, although the Euramerican region is evidently more complicated, two large plates and at least one sub-plate may possibly be distinguished within it.…”
Section: Introductionmentioning
confidence: 99%
“…As Skevington (1971, p. 286) points out, the possibility that the specimen is incorrectly localized should be investigated in view of the Arenig to Llanvirn or Llandeilo age suggested for the Macduff Group by Downie et al (1971) on the basis of microfossils. Similarly the isotopic age data summarized by Dunning (1972) suggest an age of at least 501 ± 17 m.y. for the Newer Gabbros which metamorphose the Macduff Group in the south of its outcrop.…”
Section: H U G H Miller's Graptolitesmentioning
confidence: 69%